2012
DOI: 10.1177/0022034512455062
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Inequalities and Oral Health in Canada and the United States

Abstract: This paper describes and compares the magnitude of socio-economic inequalities in oral health among adults in Canada and the US over the past 35 years. We analyzed data from nationally representative examination surveys in Canada and the US: Nutrition Canada National Survey (1970-1972, N = 11,546), Canadian Health Measures Survey (2007-2009, N = 3,508), The First National Health and Nutrition Examination Survey (1971-1974, N = 13,131), and National Health and Nutrition Examination Survey (2007-2008, N = 5,707)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 18 publications
7
90
2
1
Order By: Relevance
“…Finland is a welfare state where the psychological impact of income inequality, relative deprivation and job insecurity on health behaviours are less severe than in other industrialized countries [Marmot, 2005;Marmot and Wilkinson, 2006]. However, we were still able to observe differences in dental caries and related behaviours between different education groups, though less steep than those reported elsewhere [Vehkalahti et al, 1991;Sabbah et al, 2009;Elani et al, 2012]. This observation highlights the importance of the contribution of formal education as a marker of socioeconomic position to health and dental behaviours.…”
Section: Discussioncontrasting
confidence: 52%
“…Finland is a welfare state where the psychological impact of income inequality, relative deprivation and job insecurity on health behaviours are less severe than in other industrialized countries [Marmot, 2005;Marmot and Wilkinson, 2006]. However, we were still able to observe differences in dental caries and related behaviours between different education groups, though less steep than those reported elsewhere [Vehkalahti et al, 1991;Sabbah et al, 2009;Elani et al, 2012]. This observation highlights the importance of the contribution of formal education as a marker of socioeconomic position to health and dental behaviours.…”
Section: Discussioncontrasting
confidence: 52%
“…The Elani, et al article was selected because it discussed the frequency of edentulism [4]. Although it is not indicated in the article how the individuals became edentulous, it was implied that there was periodontal disease, based on the fact that the other factors that were being studied were disease of the teeth or solutions for tooth disease.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles [4,12] discussed socio-economic inequalities by comparing the loss of teeth to periodontal disease and other dental maladies over a given period of time. Elani, et al, which compared Canada to the US, concluded that even though there was a decrease in equalities for both Canada and the US from 1972, the start of the study and 2007-08, its conclusion, the rate of edentulism increased in the US for socially disadvantaged groups [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations